2019
DOI: 10.1200/jco.2019.37.15_suppl.9547
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab as first-line therapy in patients with unresectable cutaneous squamous cell carcinoma (cSCC): Phase 2 results from CARSKIN.

Abstract: 9547 Background: Cemiplimab, a PD-1-axis blocking agent, has recently been approved for unresectable cSCCs. We report results of the CARSKIN study evaluating pembrolizumab in the first-line setting. Methods: Chemotherapy naive patients (pts) with unresectable cSCCs, either locally or regionally advanced or metastatic, and ECOG PS ≤1 were accrued to this multi-institutional phase II trial to assess tumor response rate (RR) and safety of pembrolizumab administered IV (200 mg Q3W) for a period up to 24 months (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
1
22
0
1
Order By: Relevance
“…However, detailed guidelines for indication are still missing which might be-at least in part-due to a lack of appropriate clinical studies for patients with recurrent or metastasised CSCC [27]. Steeb et al reviewed the previous studies and experiences using checkpoint inhibitors in advanced CSCC and concluded that cemiplimab and pembrolizumab immunotherapy could result in a response rate of 40-55% in a first-line palliative setting [27][28][29]. These promising results might be due to a high immunogenicity of CSCC [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, detailed guidelines for indication are still missing which might be-at least in part-due to a lack of appropriate clinical studies for patients with recurrent or metastasised CSCC [27]. Steeb et al reviewed the previous studies and experiences using checkpoint inhibitors in advanced CSCC and concluded that cemiplimab and pembrolizumab immunotherapy could result in a response rate of 40-55% in a first-line palliative setting [27][28][29]. These promising results might be due to a high immunogenicity of CSCC [30].…”
Section: Discussionmentioning
confidence: 99%
“… 6 Similarly, pembrolizumab has achieved in a recent phase II study a 38.5% response rate, with excellent tolerability. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Four prospective phase II studies and one phase I study were identified. [3][4][5][6][7][8] The remaining records included one expanded-access programme, two retrospective analyses and 22 case reports or series. The number of patients per study ranged from one to 137.…”
mentioning
confidence: 99%
“…Cemiplimab and pembrolizumab appear to be the most evidencebased substances in this setting, as they yielded response rates consistently from 40% to 55% and were investigated in methodological studies of higher quality. [3][4][5][6][7][8] We also contacted the authors of the included studies, who consistently confirmed the use of cemiplimab as the current standard of care for advanced cSCC. Other agents of ICB also showed promising clinical results with objective and durable responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation